Temperature field simulation and ampacity optimisation of 500 kV HVDC cable. Issue 16 (14th January 2019) - Zhou, Boda; Le, Yanjie; Fang, Yalin; Yang, Fan; Dai, Tao; Sun, Lu; Liu, Jiapeng; Zou, Lekai
Abstract : The temperature distribution of the submarine cable is an important parameter during the operation. In order to lift the efficiency of heat dissipation during the high‐voltage direct current (HVDC) cable thermal cycling test, this study presents a method of cooling the cable using a cooling pipe with circulating water. A three‐dimensional mode based on the thermal‐fluid coupled model was established for 500 kV HVDC submarine cable by using finite element simulation software COMSOL Multiphysics and Fluent. The temperature field distribution and carrying ampacity of the HVDC submarine cables were analysed and compared under two cooling modes including bipolar double pipe and bipolar single pipe. The results indicate that both cooling modes can lift the current carrying ampacity of the cable; the bipolar double tube cooling mode performs better in cooling, a tiny circulating water velocity can significantly reduce the temperature of the submarine cable. Thus both suitable cooling mode and circulating water velocity were determined to accelerate the heat dissipation of the submarine cable during the thermal cycling test.